Analisis Distribusi Tingkat Keparahan Keluhan Subjektif Muskuloskeletal Diseases (Msds) Dan Karakteristik Faktor Tingkat Risiko Ergonomi Pada Pekerja Kantor Asuransi - LARIF JAUHARI; KUAT PRABOWO; ARFIA FRIDIANTI (JURNAL INFO KESEHATAN, 2017)
Occupational health is the right of every worker to be guaranteed by the business owner. Workers are free to choose the type of work so as to obtain fair and prosperous working conditions. In the scope of occupational health prosperous has a very broad meaning covers all aspects of life ranging from health, safety, tranquility, feasibility and comfort in work (PP No.50, 2012). One of the hazards of occupational health is the danger of ergonomics. The objective of the paper was to analyze factors related to subjective complaints of musculoskeletal disorder (MSDS) disease in insurance company workers. This research is a quantitative analytic research using cross-sectional study design because in this research the data collection of the dependent variable and the independent variable is observed in the period of time together. The results showed that the description of the distribution of complaints entered the Medium category. Individual factors picture of complaints at age 36-45 years of male sex and tenure> 3 years. A description of the REBA ergonomic risk factor level was obtained by the final score of 7 (Medium) and 9 (High). The description of work equipment according to CSA standards and relationship test results for individual factors on the variable age and service period there is a significant relationship, while for gender variables there is no significant relationship. For test result of REBA risk factor factor and labor factor factor test, there was no significant correlation with severity of MSDs disease subjective severity.